Analisa Break Even Point Produk Jus Pala Pada UD. Tomasiwa Desa Morela Kecamatan Leihitu - Febiola Matuankotta; Join Rachel Luturmas (Jurnal Administrasi Terapan, 2023)
The purpose of this study is to calculate and analyze the Break Even Point (BEP) or principal return point in UD. Tomasiwa Morela Village, Leihitu District. UD. Tomasiwa is a business in the beverage industry that produces nutmeg juice. The production process started in 2008 until now.The analysis used in this study is Break Even Point Analysis (BEP), namely BEP in units and BEP in rupiah. From the calculation results, it was found that BEP in units (Q) amounted to 58,548 units and BEP in Rp (QP) amounted to Rp.352,723,270, - From the results of the BEP analysis or the principal return point is expected UD. Tomasiwa can be used as an input in developing company activities, especially in knowing the amount of nutmeg juice that must be produced.UD. Tomasiwa has basically produced and sold nutmeg juice in a state beyond the Break Even Point or sales above the Breakeven point, it's just that the company does not have an effective production planning method so that the company has not been able to determine the minimum sales that must be achieved. By planning a profit of 15%, UD earned. Tomasiwa will get a profit of Rp.405,631,760.50 So if UD. Tomasiwa can achieve the profit target of 15%, then UD. Tomasiwa must sell as many as 185,586 units or Rp. 405,631,760.50 But the otherwise, if UD. Tomasiwa sells below the target volume, so the profit obtained does not reach 15%.Keywords: Break Even Point